أحكام الجراد في الفقه الإسلامي: دراسة فقهية مقارنة - آل عبدالهادي، عبدالله بن عايض بن عبدالهادي (جامعة الباحة, 2021)
هذا البحث يتحدث عن أحكام الجراد في الفقه الإسلامي: دراسة فقهية مقارنة، وقد قسم الباحث بحثه إلى مقدمة، وهي تحتوي على: الافتتاحية، وأهمية الموضوع وأسباب اختياره، وأهداف البحث، وخطة البحث، وجعل الباحث الخطة إلى مبحثين، وفي كل مبحث عدة مطالب، ثم جعل الباحث المبحث الأول: في الأحكام الفقهية المتعلقة بالجراد في العبادات، وجعله في خمسة مطالب. ثم جعل المبحث الثاني: في الأحكام الفقهية المتعلقة بالجراد في المعاملات، وجعله في خمسة مطالب كذلك. ثم اختتم الباحث بحثه بأهم النتائج، ثم فهرس المصادر والمراجع، وقد بين الباحث من خلال هذا البحث أن كثيراً من المسائل المتعلقة بالجراد، محل خلاف بين الفقهاء، وقد أورد أقوال الفقهاء في كل مسألة وأدلة كل قول، ثم بين الراجح الذي ظهر له في تلك المسألة. وقد ظهر للباحث من خلال البحث حاجة الناس لمعرفة هذه الأحكام، فكثير من هذه الأحكام متعلقة بدينه، وعبادة ربه، ولها تعلق بباب العبادات، وكذلك بباب المعاملات، وظهر له كذلك سعة الشريعة الإسلامية، وشمولها لكل شؤون الحياة، وأنها صالحة لكل زمان ومكان، والحمد لله رب العالمين. The researcher divided his research into an introduction, which contains: the opening, the importance of the subject and the reasons for its selection, the objectives of the research, and the research plan. The researcher made the plan into two topics, and in each topic, there are several requirements, Then the researcher made the first topic which addresses the jurisprudential provisions related to locusts in worship, and made it into five requirements. Then he made the second topic which addresses jurisprudential provisions related to locusts in transactions and made it into five requirements as well. Then the researcher concluded his research with the most important results, then the index of sources and references, The researcher has showed, through this research, that many issues related to locusts are subject to disagreement among jurists, and he mentioned the sayings of jurists in every matter and evidence of every saying and showed the outweighing opinion according to his view in this matter. The researcher realized, through the research, the need of people to know these provisions, whereas many of these provisions are related to their religion and the worship of their Lord, and they have to do with the acts of worship, as well as transactions, and he also realized the capacity of Islamic law, and its coverage of all life affairs, and that it is valid for every time and place.
Keywords: أحكام الجراد -- الشريعة الإسلامية -- الاختلاف الفقهي -- أصول الفقه الإسلامي